Improvement of Rights to Buildings Property to Be Living House at Land Office in the Pekalongan City - Karsono Karsono; Desi Ana Yustianita; Achmad Sulchan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to analyze: 1) the implementation of the improvement of the status Broking become Properties for Residential Land Offices Pekalongan. 2) Barriers and solutions in the implementation of the improvement of the status Broking become Properties for residences in the Land Office Pekalongan. Method approach in this study is juridical sociological. The data used are primary and secondary data obtained through interviews and literature, while data analysis was done by descriptive analysis.Results of the research results can be concluded: 1) The increase in status Broking become Properties for Residential Land Offices Pekalongan begins from filling the application letter, attaching a land certificate, a copy of building permit, a letter from the village head, a copy of the letter Tax Payable (SPPT), copy of land and Building Tax (PBB), Examination Identity applicant agree or disagree with land ownership being requested, research documents received, the applicant made a payment, examine documents and land book certificate new, then Head of surrender documents and land books and certificates to the officers of sub. PHI to do the bookkeeping and when it is complete then the clerk handed the documents to be archived to the archive officer, and submit a certificate to the applicant. 2) The difficulties experienced that an applicant seeking to register an increase in land rights for residences often do not include the application for the building permit, the public is less aware of the procedures and conditions should be attached at the time of filing the application. The solution that the Land Office of Pekalongan socialization, it aims to provide information and understanding to the community.Keywords: Improved Status of Land; Right of Building Usage; Owner Right.